Model Teologi Strategis Diakonia Berbasis Pemikiran Kennon L. Callahan bagi Gereja di Indonesia - Yustinus Yustinus (Sekolah Tinggi Theologia Nazarene Indonesia, 2026)
The study arises from the contextual reality of churches facing tensions between their missional calling, limited resources, and the demand for sustainable diaconal ministry. However, diaconal studies in Indonesia still lack an integrative theological framework that connects normative reflection with contextual strategic planning. This research employs a qualitative conceptual approach within the framework of practical theology, using critical analysis of literature on diaconal theology, missio Dei, and strategic church planning. The findings indicate that determining the focus of diaconal ministry should not be understood merely as a managerial consideration, but as a theological decision in interpreting God’s calling amid concrete limitations. Through a contextual analysis of Callahan’s principle of focused ministry, this study argues that strategic planning gains theological significance when situated within the framework of the missio Dei. Accordingly, strategic diaconal theology is proposed as a practical theological framework that guides churches in shaping diaconal ministry that is contextual, focused, and sustainable.